Relationships between corporate sustainability initiatives on employees and financial performance of companies in Malaysia - Obeitoh, Ozigi Omoyi (2018)
The study investigates the level of corporate sustainability disclosure on employee and the extent to which such disclosure influences financial performance of companies. The study examines relationship between five dimensions of corporate sustainability initiatives on employees and financial performance. The study covers a six year period of 2010 to 2015 of 253 public listed companies in Malaysia. This study employs two-step system generalized method of moment (GMM) for analysis. The findings reveal a low level of employee disclosure by companies in Malaysia which is consistent with previous studies. The study establishes the need for government involvement to enhance disclosure as voluntary disclosure appears to be inadequate to achieve the desired result as evidence shows that countries where disclosure is compulsory have high disclosure compare to countries with voluntary disclosure. The result of the study indicates strong association between some measures of financial performance and some dimensions of corporate sustainability disclosure on employees. It also establishes the importance of employee welfare in corporate sustainability disclosure on employee. Employee welfare has strong relationship with NPM, ROE and EPS. In addition, the dimensions of employee welfare, employee workplace and employee human rights show consistent results with NPM, ROE and EPS.It also demonstrates the importance of corporate sustainability initiatives on employee in maintaining competitive advantage, industrial harmony, employee loyalty and commitment which can improve financial performance.